2017
DOI: 10.1002/2016jd025599
|View full text |Cite
|
Sign up to set email alerts
|

An improved ray theory and transfer matrix method‐based model for lightning electromagnetic pulses propagating in Earth‐ionosphere waveguide and its applications

Abstract: An improved ray theory and transfer matrix method‐based model for a lightning electromagnetic pulse (LEMP) propagating in Earth‐ionosphere waveguide (EIWG) is proposed and tested. The model involves the presentation of a lightning source, parameterization of the lower ionosphere, derivation of a transfer function representing all effects of EIWG on LEMP sky wave, and determination of attenuation mode of the LEMP ground wave. The lightning source is simplified as an electric point dipole standing on Earth surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(66 citation statements)
references
References 47 publications
(94 reference statements)
0
65
0
Order By: Relevance
“…For nighttime conditions, β is set to 0.8 km −1 and h ′ is set to 84 km, while for daytime conditions β is set to 0.3 km −1 and h ′ is set to 70 km. The adopted values of h ′ and β are the same as those used by Qin et al () (see their Table ) in computing the field waveforms shown in their Figures 4 and 5. Equation overestimates the ionospheric conductivity at h > 90 km or so, but this does not influence any of our results, which remain essentially the same when the conductivity is capped at 1 S/m for h > 90 km.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…For nighttime conditions, β is set to 0.8 km −1 and h ′ is set to 84 km, while for daytime conditions β is set to 0.3 km −1 and h ′ is set to 70 km. The adopted values of h ′ and β are the same as those used by Qin et al () (see their Table ) in computing the field waveforms shown in their Figures 4 and 5. Equation overestimates the ionospheric conductivity at h > 90 km or so, but this does not influence any of our results, which remain essentially the same when the conductivity is capped at 1 S/m for h > 90 km.…”
Section: Methodsmentioning
confidence: 99%
“…In other words, the entire computational domain above ground is assumed to be lossy and nonuniform, but isotropic and linear. In section 4, we will test the validity of our simplified approach against measurements presented by Qin et al () and show that it is justified, at least for daytime conditions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations